The Preventive Power of the Mediterranean Diet Against Blue-Light-Induced Retinal Degeneration: Is the Secret in the Herbs and Spices? - Anja Harej Hrkać; Ana Pelčić; Tea Čaljkušić-Mance; Jasenka Mršić-Pelčić; Kristina Pilipović (Current Issues in Molecular Biology, 2025)
The Mediterranean diet, rich in plant-based foods, healthy fats, and herbs, has long been associated with a range of health benefits, including cardiovascular, neuroprotective, and anti-inflammatory effects. Recent studies suggest that certain components of this diet, particularly spices such as bay laurel, thyme, oregano, sage, and rosemary, may play a critical role in protecting the retina from oxidative damage, a key factor in blue-light-induced retinal degeneration. Blue light, emitted by digital screens and artificial lighting, has been implicated in the development of retinal conditions like age-related macular degeneration by inducing oxidative stress and inflammation. This review explores the potential of the herbs and spices commonly present in the Mediterranean diet to mitigate blue-light-induced retinal damage. These herbs are rich in polyphenols, flavonoids, essential oils, and terpenes, which offer antioxidant, anti-inflammatory, and antimicrobial properties, contributing to retinal health and reducing oxidative damage. By focusing on bioactive compounds such as eucalyptol (1,8-cineole), rosmarinic acid, carnosic acid, eugenol, and thymol, this article investigates how these herbs and spices might act as natural protectants against blue-light-induced stress and retinal degeneration. The findings highlight the promising role of these culinary staples in preventing retinal damage and offer insights into future dietary recommendations for eye health in an increasingly digital world.